Astilbin toxicity to leaf-cutting ant Atta sexdens rubropilosa (Hymenoptera: Formicidae) - Cintra, P. [UNESP]; Bueno, F. C. [UNESP]; Bueno, O. C. [UNESP]; Malaspina, O. [UNESP]; Petacci, F.; Fernandes, J. B. (My University, 2005)
The toxicity of astilbin, isolated from Dimorphandra mollis, was tested in laboratory ingestion bioassays for the leaf-cutting ant Atta sexdens rubropilosa Forel. Worker ants that were fed an artificial diet daily to which astilbin was added had a higher mortality rate than the controls. The substance astilbin was incorporated into the diet with and without the utilization of a solvent. Results for both methodologies utilized were similar and indicate that astilbin reduces the median survival of ants. All concentrations tested showed toxic effects against ant workers, and the statistical comparison of survivorship rates from control and treated groups was significantly different, confirming the insecticidal properties of the substance astilbin.
Keywords: Astilbin; Dimorphandra mollis; Insecticidal activity; Leaf-cutting ant; Atta; Atta sexdens rubropilosa; Formicidae; Hymenoptera